Förskollärares konstruktion av ett fysikaliskt lärandeobjekt - Lina Hellberg; Susanne Thulin; Andreas Redfors (Nordina: Nordic Studies in Science Education, 2019)
In 2010 the Swedish national curriculum was revised and learning goals concerning chemistry and physics were introduced. That has induced a need for further understanding of teaching and learning of specific content in preschool. Focus in this article is how physics content is constructed as an object of learning during preschool teachers’ planning of teaching. The result of a phenomenographic analysis focusing themes of the conversation concerning the intended object of learning reveals a complex process. Occurrences in the activities with the children, available tools at the preschool, the preschool teachers’ perceptions of the mission and understanding of the learning object, contribute to the construction of the learning object. All these aspects are discussed and implications for preschool practice are suggested.